Noninvasive prenatal testing: more caution in counseling is needed in high risk pregnancies with ultrasound abnormalities. (May 2016) - Oneda, Beatrice; Steindl, Katharina; Masood, Rahim; Reshetnikova, Irina; Krejci, Pavel; Baldinger, Rosa; Reissmann, Regina; Taralczak, Malgorzata; Guetg, Adriano; Wisser, Josef; Fauchère, Jean-Claude; Rauch, Anita
Abstract: Objective: Non-invasive prenatal testing (NIPT) is increasingly being used in prenatal aneuploidy screening. The objective of this study was to assess the positive predictive value in our cohort of 68 cases with positive NIPT result. In addition, we wondered if the use of NIPT in cases with ultrasound abnormalities is appropriate, given the limited number of chromosomes investigated. Design: We performed confirmative invasive testing using karyotyping, fluorescence in situ hybridization (FISH) and/or high-resolution chromosomal microarray analysis. Results: In line with the published data, the positive NIPT result was confirmed in 64.7% of cases. Inconclusive and negative NIPT results followed by cytogenetically pathologic findings were encountered in three and in five cases, respectively. Four of the five fetuses with negative NIPT but pathologic cytogenetic findings were born with several malformations and diagnosed right after birth with severe genetic conditions. Of note, in all of those four cases, NIPT was offered despite the finding of major fetal ultrasound abnormalities and despite the fact that the family would not have opposed invasive testing or pregnancy termination. Conclusion: More education of health care providers and caution in counseling and interpretation of test results are needed in order to meet the challenges that this new test, which enriches our diagnostic options in prenatal testing, poses.